Effect of vorapaxar on cardiovascular and limb outcomes in patients with peripheral artery disease with and without coronary artery disease: Analysis from the TRA 2°P-TIMI 50 trial. (April 2020) - Qamar, Arman; Morrow, David A; Creager, Mark A; Scirica, Benjamin M; Olin, Jeffrey W; Beckman, Joshua A; Murphy, Sabina A; Bonaca, Marc P
Intensive antithrombotic therapy reduces major adverse cardiovascular events (MACE) and major adverse limb events (MALE) in patients with peripheral artery disease (PAD). Recent studies have suggested heterogeneity in risk and benefit in those with and without concomitant coronary artery disease (CAD) and peripheral revascularization. We evaluated the risk of MACE and MALE in patients with PAD stratified by history of concomitant CAD and prior peripheral revascularization and whether the efficacy and safety of vorapaxar were similar in these subgroups. The TRA 2°P-TIMI 50 trial randomized 26, 449 patients with prior MI, ischemic stroke, or PAD to vorapaxar or placebo. This analysis examined the effect of vorapaxar in a broad population of 6136 patients with PAD. Overall, vorapaxar significantly reduced MACE (HR 0.85, 95% CI 0.73, 0.99; p = 0.034) and MALE (HR 0.70, 95% CI 0.53, 0.92; p = 0.011) in patients with PAD. The absolute risk reduction (ARR) for MACE was greater in patients with PAD and CAD versus those with PAD alone (–2.2% vs 0.1%: number needed to treat (NNT) 45 vs 1000). Conversely, the ARR for MALE was higher in those with prior lower extremity revascularization (2.5% vs 0.2%: NNT 40 vs 500). Vorapaxar increased major bleeding (HR 1.39, 95% CI 1.12, 1.71; p = 0.003). The net clinical outcome in all patients with PAD was reduced with vorapaxar (HR 0.82, 95% CI 0.72, 0.94; p = 0.004), with benefits driven by reductions in MACE for those with CAD and by reductions in MALE for those with prior peripheral revascularization. Among patients with PAD, vorapaxar resulted in a net clinical benefit; however, the drivers of benefit were heterogeneous, with greater reductions in MACE in those with concomitant CAD and greater reductions in MALE in those with prior lower extremity revascularization, and unclear benefit in patients with neither. These clinical characteristics may be useful in identifying the subgroups of patients with PAD most likely to benefit from potent antithrombotic therapies.ClinicalTrials.gov Identifier: NCT00526474